RUMAH TRADISIONAL JOGLO DALAM ESTETIKA TRADISI JAWA - Slamet Subiyantoro (Fakultas Sastra Universitas Negeri Malang, 2011)
Javanese traditional house has its own aesthetics value which represents the manifestation of the Javanese’s way of life in response to the environment. Joglo as a building is a symbolic representation of reality whose values has exceeded the form and the structure of the building. Joglo in its Javanese language means to establish communication with the God either vertically or horizontally with other nature and environment